Effects of Irrigation Levels on the Yield of Chickpea (Cicer Arietinum Linn) Due to Incidence of Helicoverpa Armigera - Mehra, Keshav; Sing, Veer (Bangladesh Journal of Botany, 2021)
Effects of four different irrigation levels viz., One irrigation at 50 per cent flowering stage, one irrigation at grain filling/pod initiation stage, two irrigations (one at 50 per cent flowering + one at grain filling stage), control (without irrigation) on the incidence of gram pod borer, Helicoverpa armigera (Hubner) on chickpea were studied during Rabi, 2014-15 and 2015-16 at Research Farm, College of Agriculture, Bikaner (Rajasthan), India. Results revealed that the highest mean larval population (3.12 larvae per 5 plants) and maximum pod damage (33.24%) were recorded in the crop which was irrigated twice viz., one at 50 per cent flowering stage and second at grain filling stage. The lowest larval population (2.03 larvae per 5 plants) with minimum pod damage (8.34%) was recorded in the crop where irrigation was not given. The maximum seed yield (11.05 q/ha) was obtained from the crop which was irrigated two times and minimum seed yield (7.56 q/ha) was obtained in control. Bangladesh J. Bot. 50(4): 1203-1207, 2021 (December)